如图,AF平分∠BAC,DF平分∠BDC,求证∠AFD=1/2(∠H+∠BGC)图:
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:48:17
如图,AF平分∠BAC,DF平分∠BDC,求证∠AFD=1/2(∠H+∠BGC)图:
如图,AF平分∠BAC,DF平分∠BDC,求证∠AFD=1/2(∠H+∠BGC)
图:
如图,AF平分∠BAC,DF平分∠BDC,求证∠AFD=1/2(∠H+∠BGC)图:
证明:延长AF交DH于E点 有三角形外角定理得,∠AFD=∠FDE+∠FED=∠FDE+∠H+∠HAE
∵AF平分∠BAC DF平分∠BDC ∴∠AFD=1/2∠BDC+1/2∠BAC+∠H
∵∠BGC=∠BDC+∠ACD=∠BDC+∠BAC+∠H
∴1/2(∠BGC+∠H)=1/2(∠BDC+∠BAC+∠H+∠H)=1/2∠BDC+1/2∠BAC+∠H=∠AFD
证明:延长AF交DH于E点 有三角形外角定理得,∠AFD=∠FDE+∠FED=∠FDE+∠H+∠HAE
∵AF平分∠BAC DF平分∠BDC ∴∠AFD=1/2∠BDC+1/2∠BAC+∠H
∵∠BGC=∠BDC+∠ACD=∠BDC+∠BAC+∠H
∴1/2(∠BGC+∠H)=1/2(∠BDC+∠BAC+∠H...
全部展开
证明:延长AF交DH于E点 有三角形外角定理得,∠AFD=∠FDE+∠FED=∠FDE+∠H+∠HAE
∵AF平分∠BAC DF平分∠BDC ∴∠AFD=1/2∠BDC+1/2∠BAC+∠H
∵∠BGC=∠BDC+∠ACD=∠BDC+∠BAC+∠H
∴1/2(∠BGC+∠H)=1/2(∠BDC+∠BAC+∠H+∠H)=1/2∠BDC+1/2∠BAC+∠H=∠AFD
收起